Evaluating Adult Cystic Fibrosis Care in BC: Disparities in Access to a Multidisciplinary Treatment Centre. (29th February 2016) - Roberts, James M.; Wilcox, Pearce G.; Quon, Bradley S.
Abstract : Background . Cystic fibrosis (CF) care that is delivered through dedicated, multidisciplinary CF clinics is believed to be partly responsible for improvements in the length and quality of life of persons with CF. We hypothesized patients living farthest from a CF clinic would be seen less frequently than recommended, which would result in reduced access to guideline-recommended care and poorer health outcomes. Methods . We performed a retrospective chart review of 168 patients who accessed CF care primarily through the St. Paul's Hospital Adult CF Clinic. Subjects were stratified into four geographical groups according to the estimated one-way travel time by automobile from their home address to the clinic (<45 mins, 45–150 mins, 150–360 mins, and >360 mins). Results . There were no significant differences in pulmonary function, nutritional status, CF-related complications, or access to guideline-recommended CF pulmonary therapies between the four groups. Compared to the reference (<45 mins) group, subjects in the two farthest groups (>150 mins) were less likely to be seen in the clinic quarterly as recommended by current CF care guidelines (p = 0.002 ). Those in the farthest group (>360 mins) were at risk for more rapid decline in lung function compared to the reference group (FEV1% predicted annual change: −3.1%/year [95% CI −5.1 to −1.1] versus −0.9%/year [95% CI −1.6 to 0.1], resp., p = 0.04 ). Conclusions . Access to CF care is a challenge for individuals who live outside Metro Vancouver and has health policy implications. Further initiatives should be undertaken to ensure equitable care for people living with CF.